DETEKSI GERAK OBJEK BERBASIS PENGOLAHAN CITRA MENGGUNAKAN METODE BINARY-IMAGE COMPARISON - Matalangi Matalangi; Abdul Jalil (LPPM Poltek ST Paul, 2020)
The purpose of this study is to build the object motion detection system based on the image processing technique used a Binary-Image Comparison (BIC) method. The function of the BIC method in this study is as a decision-maker to make the system be able to send the message data as a result of object motion detection. The object motion has detected in this study is the object with a colour of red, yellow, green and blue. In this study, the image processing segmentation has been processed using OpenCV library software and was executed in the Robot Operating System 2 (ROS2) nodes. Some of the ROS2 nodes have been used to build the object motion detection on this study, that is a node to read the RGB camera input, a node to detect the red object motion, a node to detect the yellow object motion, a node to detect the green object motion, a node to detect the blue object motion, and a node to receive the result of the motion detection object. Each node in this systems will be connected to each other through a topic to make them are able to exchange the image message data using the Data Distribution Service (DDS) protocol on the ROS2. The result from this study is the systems can be detected the object motion are red, yellow, green, and blue then sent it as a message data based on the resulting process from the BCI method.